Binary Carbon Modification Promoting the Electrochemical Performance of Silicon Anode for Lithium‐Ion Batteries. Issue 6 (7th February 2023) - Feng, Yaxin; Zhang, Yang; Song, Ye; Li, Pingyun; Liu, Jie
Abstract: As the research on lithium‐ion battery cathode materials gradually breaks through the saturation, the anode materials for lithium‐ion batteries have received wide attention because of their promising future. Silicon electrodes, in particular, are attracting increasing attention. In this paper, the Si/G precursor was achieved by simple mechanical ball milling. Two silicon based composite electrode materials Si@TA and Si@TA‐G were synthesized by spontaneous polymerization of tannic acid on precursor surface in Tris buffer solution. For the poor electrical conductivity of silicon, graphite was added as a carbon source to avoid the direct contact between silicon and electrolyte during charge/discharge process by forming tannic acid coating on silicon surface.The Si@TA composites achieve a discharge specific capacity of 927.4 mAh g −1 at 100 mA g −1 current density after 50 cycles with a retention rate of 87.1 % while the reversible capacity of Si@TA‐G is 1249.8 mAh g −1 with a retention rate is 93.6 %. This unique composite method provides new insights into the modification of silicon anode materials. Abstract : Core‐shell structured silicon‐based anode materials for lithium‐ion batteries using tannic acid and graphite as carbon sources were prepared. The TA coating and graphite not only modified the structure of silicon anode, but also promoted its electrochemical stability. The composites with 93.6 % retention rate were demonstrated after 50 cycles at 100 mA g −1 .